SCHOOL-BASED YOUTH INFORMATION AND COUNSELING ACTIVITIES FOR DEVELOPING ADOLESCENT LIFE SKILLS - Siti Siska Cutikawati; Damanhuri; Ria Yuni Lestari (EDUCATIONE, 2026)
Schools require integrated approaches that enable adolescents to practice personal, social, and decision-making competencies rather than merely receive health information. This study examined how activities in an Indonesian Youth Information and Counseling Center (Pusat Informasi dan Konseling Remaja, PIK-R) were perceived to foster junior secondary students’ life skills and identified conditions supporting or constraining implementation. A descriptive qualitative case study was conducted at SMP Negeri 7 Kota Serang from October 2025 to January 2026. Data were generated through participant observation, in-depth interviews with eight informants—one PIK-R supervisor, one trainer, and six student members—and analysis of photographs, videos, organizational records, and program documents. Data were reduced, displayed, compared across sources, and interpreted through source and technique triangulation. Five interconnected activities—leadership training, self-management, life-skills training, peer educator preparation, and peer counselor preparation—were associated with six domains: physical and mental self-care, self-awareness and expression, cooperation, self-protection and assertiveness, logical decision-making, and goal planning. Adequate facilities, trained personnel, school funding, peer support, and collaboration with the population and family-development agency enabled implementation. Schedule conflicts and limited student interest restricted continuity and reach. PIK-R can function as a school-based positive youth-development setting when learning is practice-oriented, peer roles are supervised, and institutional support is sustained. Multi-site and longitudinal research should examine non-participants, program dosage, and changes measured with validated life-skills instruments.